2014
DOI: 10.1021/jp502818u
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer Dissociation Mass Spectrometry of Peptides Containing Free Cysteine Using Group XII Metals as a Charge Carrier

Abstract: Electron transfer dissociation (ETD) has been used for peptide sequencing. Since ETD preferentially produces the c'/z(•) fragment pair, peptide sequencing is generally performed by interpretation of mass differences between series of consecutive c' and z(•) ions. However, the presence of free cysteine residues in a precursor promotes peptide bond cleavage, hindering interpretation of the ETD spectrum. In the present study, the divalent group XII metals, such as Zn(2+), Cd(2+) and Hg(2+), were used as charge ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…For several acidic peptides, Asakawa and coworkers [52] demonstrated that metallated peptide ions with 2+ or 3+ charges produced by cationization with potassium or calcium ions underwent more sequence-informative ETD as compared to dissociation of the analogous protonated ions. In another study, Asakawa and Wada [53] complexed peptides containing cysteine residues with three divalent metal ions. The nature of the metal affected the production of c- and z-ions by ETD.…”
Section: Introductionmentioning
confidence: 99%
“…For several acidic peptides, Asakawa and coworkers [52] demonstrated that metallated peptide ions with 2+ or 3+ charges produced by cationization with potassium or calcium ions underwent more sequence-informative ETD as compared to dissociation of the analogous protonated ions. In another study, Asakawa and Wada [53] complexed peptides containing cysteine residues with three divalent metal ions. The nature of the metal affected the production of c- and z-ions by ETD.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a protonated precursor, metal-peptide complexes give a c'/z• fragment pair by ECD/ETD for most metal cations [13][14][15][16][17][18][19], suggesting that the fragmentation proceed via Utah-Washington model. In contrast, transition metal cations with a partially filled d orbital shell, such as Co 2+ , Ni 2+ , and Cu 2+ , are reduced by ECD/ETD [15,20].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various charge carriers, the metal ion has gained special interest because it achieves the most diverse chemistry by forming various complexes with peptides. The effect of metal ions as charge carriers for ECD fragmentation of peptides has been investigated by several groups . It has been demonstrated that metal ions could tune the ECD pathways of peptides.…”
mentioning
confidence: 99%